An Analysis of Students Misbehaviour in Distance Learning - Sari Dewi Noviyanti (Loquen, 2021)
Online learning has become an inevitable trend in the world of education. Even before the outbreak of the Covid 19 pandemic, many educational institutions had implemented blended and distance learning in their teaching and learning activities. In fact, distance learning is an innovative step that allows the transfer of knowledge without time and space boundaries. Effective distance learning cannot be separated from behaviour of students. Students discipline is a crucial element to create an effective online class situation. The study has objective of analysing misbehaviour occurred in online class. The approach used in this research is qualitative using questionnaires and interviews as data collection techniques. 10 English teachers were interviewed to obtain the data about students’ misbehaviour occurred. Furthermore, the data were analysed descriptively. The results showed that the most common students misbehaviour in online class was failure of assignment submission, language aggression and disrespecting teachers.